1985
DOI: 10.5014/ajot.39.3.143
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge for Research in a Practice Profession

Abstract: We have suggested that certain research challenges now face the profession. In summary, these challenges may be seen as part of the dual mission of research in a practice profession. Research must contribute to the development of a body of knowledge: some research is academic and theoretical in nature and other research helps to sustain and improve clinical practice. In either case, theory in a practice profession differs significantly from that in more traditional sciences. It is, in fact, more sophisticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There is an increasing demand worldwide that occupational therapy practice become evidence based (Bennett and Bennett, 2000;Cusick and McCluskey, 2000;Taylor, 2000). As a result, treatment effectiveness and outcome studies have been identified as key issues for the profession (Llorens and Gillette, 1985;Llorens and Snyder, 1987;Law, 1989a;Taylor and Mitchell, 1990;Timmerman et al, 1994;Unsworth, 2000). Active involvement of clinicians in clinical research has been advocated to facilitate professional practice that is grounded in theory and research, and provides quality care to our clients (Baum et al, 1984;Llorens and Gillette, 1985;Mitcham, 1986;Llorens and Snyder, 1987;Cusick, 1987Cusick, , 1994Cusick, , 2000Law, 1989a;Taylor and Mitchell, 1990;Rogers and Holm, 1994;Timmerman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing demand worldwide that occupational therapy practice become evidence based (Bennett and Bennett, 2000;Cusick and McCluskey, 2000;Taylor, 2000). As a result, treatment effectiveness and outcome studies have been identified as key issues for the profession (Llorens and Gillette, 1985;Llorens and Snyder, 1987;Law, 1989a;Taylor and Mitchell, 1990;Timmerman et al, 1994;Unsworth, 2000). Active involvement of clinicians in clinical research has been advocated to facilitate professional practice that is grounded in theory and research, and provides quality care to our clients (Baum et al, 1984;Llorens and Gillette, 1985;Mitcham, 1986;Llorens and Snyder, 1987;Cusick, 1987Cusick, , 1994Cusick, , 2000Law, 1989a;Taylor and Mitchell, 1990;Rogers and Holm, 1994;Timmerman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…That is, developing occupational therapy's knowledge base was and is a professional priority, to better understand the outcomes of practice, and for occupational therapy's viability (AOTA & AOTF, 2004;AOTF, 1975;Llorens & Gillette, 1985). Understanding how occupational therapy's past influences the profession today, can be explored by asking two questions.…”
Section: Section Viii: Occupational Therapy's Past Influences Its Prementioning
confidence: 99%
“…The gap between research and practice must therefore be closed if we are to develop and refine our body of knowledge (Lloyd-Smith, 1997). Therefore, as research data are used more frequently as a basis for shaping occupational therapy practice, documenting client outcomes and illustrating how occupational therapy services do make a difference in health care, the value of research will be evident and will be reflected with an enhanced professional and public image (Gilfoyle and Christiansen, 1987;Llorens and Gillette, 1985;Smith, 1989).…”
Section: Research Utilization Models: a Comparative Analysismentioning
confidence: 99%